Correlation of Mother's Outlook of Exclusive Breastfeeding and Stunting in Border Area of West-Central Java Province - Permana, Irman; Norviatin, Dini; Arumtara, Hasna Nuha; Wardhani, Faza Nurul (Newinera Publisher, 2024)
Children under five years-old (toddlers) were very vulnerable to malnutrition especially stunting. Special consideration must be given to stunting in children under the age of five, as it has a detrimental impact on their mental and physical development. One of the factors that has been linked to stunting is non-exclusive breastfeeding. Lack of exclusive breast feeding on baby can be caused by poor parenting, especially low maternal’s outlook. The aim of the study was to discover the correlation between maternal’s outlook and exclusive breastfeeding with the incidence of stunting in toddlers aged 24-59 months in Brebes city, border area of West – Central Java Province. This cross-sectional study was conducted in June 2022 in multiple integrated health service clinics (posyandu) in Kersana district, Brebes. Participants were children between the ages of 24 and 59 months who attended the posyandu and were selected using consecutive sampling. Data was taken using questionnaire and the analytical technique used Spearman correlation test. Most of respondents were aged 31-40 years (53,7%), elementary school education level (47,1%), maternal status (82,4%), and who had daughters (56,5%). The results of the Spearman correlation test showed that there was a significant relationship between the maternal knowledge (p = 0.000, r = -0.886), and exclusive breastfeeding (p = 0.000, r = -0.661) with the incidence of stunting. The study concluded that low maternal’s outlook and non-exclusive breastfeeding significantly correlated with higher incidence of stunting.